Clinician guidelines for the treatment of psychiatric disorders with nutraceuticals and phytoceuticals: The World Federation of Societies of Biological Psychiatry (WFSBP) and Canadian Network for Mood and Anxiety Treatments (CANMAT) Taskforce. (3rd July 2022) - Sarris, Jerome; Ravindran, Arun; Yatham, Lakshmi N.; Marx, Wolfgang; Rucklidge, Julia J.; McIntyre, Roger S.; Akhondzadeh, Shahin; Benedetti, Francesco; Caneo, Constanza; Cramer, Holger; Cribb, Lachlan; de Manincor, Michael; et al.
Abstract: Objectives: The therapeutic use of nutrient-based 'nutraceuticals' and plant-based 'phytoceuticals' for the treatment of mental disorders is common; however, despite recent research progress, there have not been any updated global clinical guidelines since 2015. To address this, the World Federation of Societies of Biological Psychiatry (WFSBP) and the Canadian Network for Mood and Anxiety Disorders (CANMAT) convened an international taskforce involving 31 leading academics and clinicians from 15 countries, between 2019 and 2021. These guidelines are aimed at providing a definitive evidence-informed approach to assist clinicians in making decisions around the use of such agents for major psychiatric disorders. We also provide detail on safety and tolerability, and clinical advice regarding prescription (e.g. indications, dosage), in addition to consideration for use in specialised populations. Methods: The methodology was based on the WFSBP guidelines development process. Evidence was assessed based on the WFSBP grading of evidence (and was modified to focus on Grade A level evidence – meta-analysis or two or more RCTs – due to the breadth of data available across all nutraceuticals and phytoceuticals across major psychiatric disorders). The taskforce assessed both the 'level of evidence' (LoE) (i.e. meta-analyses or RCTs) and the assessment of the direction of the evidence, to determine whether the intervention was 'Recommended' (+++), 'Provisionally Recommended' (++), 'Weakly Recommended' (+), 'Not Currently Recommended' (+/−), or 'Not Recommended' (−) for a particular condition. Due to the number of clinical trials now available in the field, we firstly examined the data from our two meta-reviews of meta-analyses (nutraceuticals conducted in 2019, and phytoceuticals in 2020). We then performed a search of additional relevant RCTs and reported on both these data as the primary drivers supporting our clinical recommendations. Lower levels of evidence, including isolated RCTs, open label studies, case studies, preclinical research, and interventions with only traditional or anecdotal use, were not assessed. Results: Amongst nutraceuticals with Grade A evidence, positive directionality and varying levels of support ( recommended, provisionally recommended, or weakly recommended) was found for adjunctive omega-3 fatty acids (+++), vitamin D (+), adjunctive probiotics (++), adjunctive zinc (++), methylfolate (+), and adjunctive s-adenosyl methionine (SAMe) (+) in the treatment of unipolar depression. Monotherapy omega-3 (+/−), folic acid (−), vitamin C (−), tryptophan (+/−), creatine (+/−), inositol (−), magnesium (−), and n-acetyl cysteine (NAC) (+/−) and SAMe (+/−) were not supported for this use. In bipolar disorder, omega-3 had weak support for bipolar depression (+), while NAC was not currently recommended (+/−). NAC was weakly recommended (+) in the treatment of OCD-related disorders; however, no other nutraceutical had sufficient evidence in any anxiety-related disorder. Vitamin D (+), NAC (++), methylfolate (++) were recommended to varying degrees in the treatment of the negative symptoms in schizophrenia, while omega-3 fatty acids were not, although evidence suggests a role for prevention of transition to psychosis in high-risk youth, with potential pre-existing fatty acid deficiency. Micronutrients (+) and vitamin D (+) were weakly supported in the treatment of ADHD, while omega-3 (+/−) and omega-9 fatty acids (−), acetyl L carnitine (−), and zinc (+/−) were not supported. Phytoceuticals with supporting Grade A evidence and positive directionality included St John's wort (+++), saffron (++), curcumin (++), and lavender (+) in the treatment of unipolar depression, while rhodiola use was not supported for use in mood disorders. Ashwagandha (++), galphimia (+), and lavender (++) were modestly supported in the treatment of anxiety disorders, while kava (−) and chamomile (+/−) were not recommended for generalised anxiety disorder. Ginkgo was weakly supported in the adjunctive treatment of negative symptoms of schizophrenia (+), but not supported in the treatment of ADHD (+/−). With respect to safety and tolerability, all interventions were deemed to have varying acceptable levels of safety and tolerability for low-risk over-the-counter use in most circumstances. Quality and standardisation of phytoceuticals was also raised by the taskforce as a key limiting issue for firmer confidence in these agents. Finally, the taskforce noted that such use of nutraceuticals or phytoceuticals be primarily recommended (where supportive evidence exists) adjunctively within a standard medical/health professional care model, especially in cases of more severe mental illness. Some meta-analyses reviewed contained data from heterogenous studies involving poor methodology. Isolated RCTs and other data such as open label or case series were not included, and it is recognised that an absence of data does not imply lack of efficacy. Conclusions: Based on the current data and clinician input, a range of nutraceuticals and phytoceuticals were given either a supportive recommendation or a provisional recommendation across a range of various psychiatric disorders. However several had only a weak endorsement for potential use; for a few it was not possible to reach a clear recommendation direction, largely due to mixed study findings; while some other agents showed no obvious therapeutic benefit and were clearly not recommended for use. It is the intention of these guidelines to inform psychiatric/medical, and health professional practice globally.